Archbishop Pecham, Thomas Bek and St. David's - Greenway, William (The journal of ecclesiastical history, 1960)
In his Ford lectures of 1955, Professor Cheney remarked that ‘Stubbs saw the church history of Richard I's reign as the record of a few great disputes at law’. One of the most notorious of these concerned the status of St. David's, whose bishop-elect, Gerald of Wales, spared no effort to acquire for his see the position of metropolitan in a separate Welsh province. It is to his lively, though partisan, account of his endeavours that we are indebted for much of our information regarding the Church in Wales at the close of the twelfth century.